Rede de solidariedade entre mulheres vítimas de violência doméstica e familiar na zona norte de Manaus - Souza, Amara Luciane Silva de (2018)
The phenomenon of domestic and family violence against women is a frequent problem in the context of contemporary society. It is a problem that reproduces, for centuries, patriarchal culture and customs, in the perspective of man exercising total domination over women. This hegemonic view of women is a vestige of a society, historically called patriarchal, with deep marks, whose roots are strongly tied to the process of formation of Brazilian society. Due to this domination that women suffer, feminist movements have emerged in search of women's rights and the construction of a new identity. In addition to the influence of a patriarchal family regime, the violence suffered by women within the domestic and family spheres is also influenced by the culture and customs of their parents, that is, their cultural heritage. Violent relations are also influenced by the social milieu, which Pierrie Bourdieu calls habitus. The purpose of this paper is to verify if there is a network of solidarity among women victims of domestic violence who were accompanied by the Maria da Penha Ronda Project from the social capital. For this purpose, a data survey was first made for the construction of the bank with information from women assisted by the Ronda Maria da Penha project, from 2014 to 2016. This database allowed to describe the profile of these women victims served by the project and to know the scenario of domestic and family violence in the area covered by the project. After the construction of the database, it was possible to verify that there were concentrations of women attended in a given locality within the scope area of the project. Thus was born the interest of interviewing these women to know if there are connections between them given from the existing social capital. Thirteen women were selected who were located in these concentrations and thus managed to interview seven of them, since some had changed address and one of them had passed away. The considerations made here take as a north the importance of the Ronda Maria da Penha project for the propagation of the social capital of these women who are served by the project, since the project is a source of resources that benefit women who suffer domestic and family violence.